(3OjhGf HgGA GdOjf RgjQs - (3GdHgGA RgjQ , RgjQ Hf eMeO Hf Ydj GdegdHj GdUGdMj, HgGA GdOjf,J (B656 (3g` s ((3eMeO Hf jMji s)
(3ChdgG (B:s
(3GdMeO ddg GdPj NU HGdaVGFd ef TGA ef GdYHGO, hChd GdTYQ Ydi bGajI GdCda bhdg(B: (3LRi Gddg Yfj GdMH NjQkG aEfg Hg EROGO bOQj aj GdCfGe hYdjGFj s
(3BNQgG (B:s
(3ef bUjOI dg ef eLRhA GdQed(B: (3jG dgG djdI hUd eKdgG dG jJgjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ GdLRA GdChd HQbe (B291 (3COHs
(3fSNI eVHhWIs
(3hocJHJ GdYfGhjf HGdMeQIs
(3oeJQH Ydi MQha GdoeYLe s
(3hQOJ CjVkG JMJ Qbe (B2202 s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs